2022
DOI: 10.18203/2320-1770.ijrcog20220167
|View full text |Cite
|
Sign up to set email alerts
|

A study of adequacy of informed consent before caesarean section in a tertiary care hospital

Abstract: Background: Informed consent is an ethical and legal requirement and is practiced before all the surgical procedures. Caesarean section is the commonest obstetric surgery so, this study was aimed to assess the adequacy of informed consent in patients who underwent caesarean section at SMGS Hospital, GMC, Jammu.Methods: A cross-sectional study was done. A total of 230 patients were included in the study. A pre-tested and pre-validated questionnaire was used for the study. The data were expressed as percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…1 ). Globally, available literature from other medical specialties reports similar results as there are gross variations in the information given before consent to different medical treatments [ 37 – 42 ]. In a tertiary care hospital in India, Bhushan and Manhas noted that although the majority of the patients were informed about the procedure, indication, benefits, and risks, very few were aware of their options for alternative procedures and the right to refuse the procedure before cesarean Sect.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1 ). Globally, available literature from other medical specialties reports similar results as there are gross variations in the information given before consent to different medical treatments [ 37 – 42 ]. In a tertiary care hospital in India, Bhushan and Manhas noted that although the majority of the patients were informed about the procedure, indication, benefits, and risks, very few were aware of their options for alternative procedures and the right to refuse the procedure before cesarean Sect.…”
Section: Discussionmentioning
confidence: 93%
“…In a tertiary care hospital in India, Bhushan and Manhas noted that although the majority of the patients were informed about the procedure, indication, benefits, and risks, very few were aware of their options for alternative procedures and the right to refuse the procedure before cesarean Sect. [ 37 ]. In Ethiopia, Chane and colleagues also, reported that only 8.1% of the patients who underwent surgery had received the minimum required components of informed consent that included type of the surgery, benefits, risks of the procedure, and alternative options of treatment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%